Use of Edpuzzle Learning Videos for class 9 Biology and its impact on academic performance - Kinga Tshering; Kesang Wangchuk; Nima Dorji; Kelzang Dema (Northern Negros State College of Science and Technology (NONESCOST), 2022)
This study examined effectiveness of Edpuzzle Learning Videos in class 9 Biology. The study employed quasi-experimental design and study used purposive sampling consisting of 30 students in grade 9. The research participants consist of two groups, namely control (Lecture method) and experimental (Edpuzzle) consisting of 15 students in each group. To collect data pre-test and post-test were administered. Data collected were analysed employing descriptive statistics. A normality test determined the distribution of data. Further, test score analysis for pre-test indicated that students in the control group (M=7.0667) and experimental group (M = 6.4667) had a similar level of knowledge. However, analysis of post-test revealed that there were substantial differences between control group (M = 8.2667, SD = 1.94447) and experimental group (M = 12.6000, SD = 1.24212). The finding of the study revealed that employing educational technology such as Edpuzzle Learning Videos proved effective in learning Biology for Middle Secondary School. Moreover, academic score increased on the post-test as a result of the student's active participation and engagement in their studies. Additionally, students were involved in learning at their own pace resulting in enhancing cognitive skills. This study recommended that Science teachers to use educational technology such as Edpuzzle Learning Videos as an alternative to conventional methods.